2023
DOI: 10.1097/iae.0000000000003686
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Evidence for the Safety of Fovea-Involving Half-Dose Photodynamic Therapy for Chronic Central Serous Chorioretinopathy

Abstract: Supplemental Digital Content is Available in the Text.None of the chronic central serous chorioretinopathy patients who received a single treatment with fovea-involving half-dose photodynamic therapy in two randomized clinical trials showed signs of developing foveal atrophy after treatment. This adds to the evidence that half-dose photodynamic therapy is a safe long-term treatment for chronic central serous chorioretinopathy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Recent retrospective analysis of chronic CSCR half-dose PDT RCT data showed that patients who underwent fovea-involving PDT had no evidence of subsequent foveal atrophy or vision loss, and instead demonstrated significant anatomic and visual improvement. This effect was seen at a mean follow-up of 22.1 months, suggesting foveal involvement in safety-enhanced PDT protocols may have long-term safety and efficacy 32 …”
Section: Photodynamic Therapymentioning
confidence: 88%
See 1 more Smart Citation
“…Recent retrospective analysis of chronic CSCR half-dose PDT RCT data showed that patients who underwent fovea-involving PDT had no evidence of subsequent foveal atrophy or vision loss, and instead demonstrated significant anatomic and visual improvement. This effect was seen at a mean follow-up of 22.1 months, suggesting foveal involvement in safety-enhanced PDT protocols may have long-term safety and efficacy 32 …”
Section: Photodynamic Therapymentioning
confidence: 88%
“…This effect was seen at a mean follow-up of 22.1 months, suggesting foveal involvement in safetyenhanced PDT protocols may have long-term safety and efficacy. 32 While PDT has demonstrated efficacy in multiple trials for chronic CSCR, its efficacy as an early treatment for acute CSCR is less clear, and many practitioners will observe acute CSCR given its high rate of spontaneous resolution. A recent small single-center trial provided some evidence to support this practice.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Interestingly, MPL and focal laser were performed more frequently than PDT even though recent large randomized controlled trials, such as the PLACE and SPECTRA trial, found PDT to be superior to other treatment options [19, 20]. PDT also shows favorable long-term safety data [21] and can safely be performed bilaterally within a single treatment session [22]. While it is thus often considered the treatment of choice [4, 23], its use in our German study population was surprisingly low.…”
Section: Discussionmentioning
confidence: 99%
“…To exclude the development of atrophy in the area treated with ssbPDT, the integrity of the external limiting membrane (ELM) and ellipsoid zone (EZ) was graded as described before. 20 In brief, eyes that had undergone fovea-involving ssbPDT and showed complete SRF resolution at the first follow-up and no recurrence, ELM and EZ integrity was graded as continuous/regular, interrupted/irregular, or indiscernible before and after treatment. Examples of these definitions were previously published.…”
Section: Methodsmentioning
confidence: 99%
“…This is further supported by evidence from our group that patients included in the PLACE trial did not develop RPE atrophy at 2 years after PDT. 20 Of note, 16 eyes of 12 patients had received intravitreal anti-VEGF injections. Only in a small minority of these, however, a secondary CNV was confirmed by the tertiary referral center (five eyes of four patients).…”
Section: Single-session Bilateral Pdt For Ccsc Pauleikhoff Et Almentioning
confidence: 99%